Caracterização biológica, morfológica e molecular de isolados de Baculovírus selecionados para o controle de Lepidópteros praga das culturas da soja e do milho - Souza, Fernando Mantouvane Lanza (2022)
Corn (Zea mays L) and soybean (Glycine max) are important commodities in Brazil. However, the attack of lepidopteran pests such as, Chrysopterais includens (Walkerdeix, 1857), Spodoptera frugiperda (Smith, 1797) and Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) can result in economic damages. Biological control with baculovirus (Bv) is an effective alternative for crop protection, therefore, identifying and selecting isolates can guarantee the durability of this strategy. Thus, this work aims to characterize in biologic, morphologic and molecular strategies isolated from baculovirus selected to control lepidopteran pests. Six Bv isolates were selected by the Bv Bank of Embrapa from preliminary results (Iso. 6, 18 and 19 for S. frugiperda, Iso. Br2 and Br8 for H. armigera and Iso. 15 for C. includens). The bioassays confirmed the efficiency of the isolates, with above 90 % mortality rate for all. The occlusion bodies of the six isolates were purified and morphologically characterized by Scanning Electron Microscopy, indicating polyhedral characteristics for all isolates. Four DNA extraction methodologies were tested, O'Reilly et al. (1992) showed be more efficient than the three commercial kits ((Quick-DNATM Viral Kit (Zymo Research®: D3015), PureLinkTM Viral RNA/DNA Mini Kit (Invitrogen®: 12280050) e QIAamp® vírus kit (Qiagen®: 57704)). The DNA of the six isolates were digested with HindIII enzyme and analyzed for similarity and genetic clustering by BLASTN using the lef8 and lef9 core genes of S. frugiperda and H. armigera isolates. The genome of isolate 15 was sequenced by the DNBSEQ (BGI) platform and a phylogenetic tree was constructed. The results indicates that S. frugiperda isolates 6 and 19 did not lose their characteristics, remaining as SFMNPV isolate 6 NR and SFMNPV isolate 19. Isolate 18 has high similarity with isolates 6 and 19 and was characterized as Aphabaculovirus Group I and Multiple Nucleopolyhedrovirus (SFMNPV isolate 18). The Br8 isolate has high similarity with Br2, however, it differs according to the genetic grouping and was characterized as Aphabaculovirus Group II and Single Nucleopolyhedrovirus (HearNPV isolate Br8). The isolate 15 has high similarity with ChinNPV–IF, however, SNPs studies are recommended to identify possible differences. It was characterized as Aphabaculovirus Group II and Single Nucleopolyhedrovirus (ChinNPV isolate 15).